Organic Fertilizers - History, Production and Applications 2019
DOI: 10.5772/intechopen.86716
|View full text |Cite
|
Sign up to set email alerts
|

The State of the Soil Organic Matter and Nutrients in the Long-Term Field Experiments with Application of Organic and Mineral Fertilizers in Different Soil-Climate Conditions in the View of Expecting Climate Change

Abstract: Soil organic matter (SOM) plays an important role in the terrestrial ecosystems and agroecosystems. Changes in the agricultural sector in the countries of the Central and Eastern Europe (the Czech Republic, Slovakia, Poland, etc.) within the past 25 years have negatively affected the SOM and contributed to the soil degradation. The aim of this chapter is the evaluation of the long-term application of mineral fertilizers and farmyard manure: the Control (without fertilization), farmyard manure (FYM + 0), FYM ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 56 publications
(55 reference statements)
2
17
0
Order By: Relevance
“…This agrees with other studies (e.g. Menšík, Hlisnikovský, & Kunzová, 2019) that have also shown that SOM content can increase following the application of manure and, overall, the use of organic amendments such as FYM or GM may improve the availability of nutrients and soil properties (Hargreaves & Warman, 2008). This change to the edaphic environment likely had consequences for the microbial communities present, changing their structure and thus impacting on soil functions and their interactions with the applied digestate.…”
Section: Discussionsupporting
confidence: 91%
“…This agrees with other studies (e.g. Menšík, Hlisnikovský, & Kunzová, 2019) that have also shown that SOM content can increase following the application of manure and, overall, the use of organic amendments such as FYM or GM may improve the availability of nutrients and soil properties (Hargreaves & Warman, 2008). This change to the edaphic environment likely had consequences for the microbial communities present, changing their structure and thus impacting on soil functions and their interactions with the applied digestate.…”
Section: Discussionsupporting
confidence: 91%
“…SOM content is intricately interlinked with other physical, chemical, and biological properties and processes. A long-term study in eastern Europe (the Czech Republic, Slovakia, and Poland) indicated that regular applications of organic manure and of manure plus chemical fertilizers optimized soil quality, stabilized crop yield, and enhanced adaptation to climate change (Menšík et al 2019).…”
Section: Soil Organic Matter Contentmentioning
confidence: 99%
“…Low precipitation in July and August 2018 together with high air temperatures affected JEV as well as the Central Bohemian Highlands (SKO) and led to early harvesting [72]. Regularly recurring dry periods during the growing season, which are recorded in the last decade not only in the Czech Republic but also in Europe, may significantly affect primary production in the future [16,17]. Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of global warming, a decline in crop yields has been recorded [8][9][10][11]. These changes are also confirmed by model studies, which predict that potential production of food and feedstuff, including maize, will be further reduced in the future [12][13][14][15][16][17]. It is expected that European countries will not be as affected as other parts of the world [18].…”
Section: Introductionmentioning
confidence: 86%